2022
DOI: 10.1038/s41598-022-16170-x
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic features of bioburden serve as outcome indicators in combat extremity wounds

Abstract: Battlefield injury management requires specialized care, and wound infection is a frequent complication. Challenges related to characterizing relevant pathogens further complicates treatment. Applying metagenomics to wounds offers a comprehensive path toward assessing microbial genomic fingerprints and could indicate prognostic variables for future decision support tools. Wound specimens from combat-injured U.S. service members, obtained during surgical debridements before delayed wound closure, were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Only wounds that can overcome initial pro-inflammatory environments regardless of colonization status and properly balance the proliferative processes through coordinated processes heal. Beyond providing more information to the wound healing process, these data provide novel functions and individual biomarkers (i.e., differentially expressed genes between failed vs. healed wounds) that can be further evaluated and incorporated into machine learning models to predict when to close the wound and whether or not there are early signs that the wound has a higher likelihood of failure as has been demonstrated previously 12 , 13 , 20 . These types of investigations will lay the foundation for precision medicine tools to improve clinical outcomes in traumatic wound care for both combat casualties and in civilian trauma centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only wounds that can overcome initial pro-inflammatory environments regardless of colonization status and properly balance the proliferative processes through coordinated processes heal. Beyond providing more information to the wound healing process, these data provide novel functions and individual biomarkers (i.e., differentially expressed genes between failed vs. healed wounds) that can be further evaluated and incorporated into machine learning models to predict when to close the wound and whether or not there are early signs that the wound has a higher likelihood of failure as has been demonstrated previously 12 , 13 , 20 . These types of investigations will lay the foundation for precision medicine tools to improve clinical outcomes in traumatic wound care for both combat casualties and in civilian trauma centers.…”
Section: Discussionmentioning
confidence: 99%
“…Further, infected wounds, such as those with either bacterial, or invasive fungal infections, frequently have more complications and worse outcomes, requiring additional surgeries or even amputation 19 . Our group has previously investigated the influence of microbial colonization in combat casualty extremity wounds using metagenomic sequencing 20 . It was found that there was not a single defining microbial profile that was associated with failed wounds, but trends such as Pseudomonas and Acinetobacter colonization were seen at higher prevalence, as well as lower observed alpha and beta diversities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have only been two reports of isolation of Mycoplasma canis from dog bite wounds in humans [6,7] and one report of the isolation of M. canis and Mycoplasma spumans from a dog bite wound in a cat. Recent advances in culture-free sequencing of clinical material have advanced the aetiological diagnosis of infectious diseases [8][9][10][11] and wound infections [12][13][14][15], and ultimately are likely to lead to improved treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…canis and Mycoplasma spumans from a dog bite wound in a cat. Recent advances in culture-free sequencing of clinical material have advanced the aetiological diagnosis of infectious diseases [8–11] and wound infections [12–15], and ultimately are likely to lead to improved treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%